Exploration of Lichen Species in the Minanga Waterfall Area, Rantau Balai Village, Aranio Subdistrict, South Kalimantan - Dian Nesty Pratiwi; Sari Indriyani; Norfajrina Norfajrina (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Lichens are symbiotic organisms formed by the union of fungi and algae or cyanobacteria that play an important role in ecosystems, including as bioindicators of environmental quality, pioneers in soil formation, and producers of bioactive compounds. The Minanga Waterfall area, located in Rantau Balai Village, Aranio Subdistrict, Banjar Regency, has a humid, shaded environment with relatively low pollution levels, making it a potential habitat for various lichen species. This study aims to identify the lichen species found in the Minanga Waterfall area. The research was conducted using an exploratory survey method with purposive sampling and transect surveys along predetermined observation routes. Data were obtained through direct observation, documentation, morphological identification, and literature review to determine the species found. The results showed that 14 lichen species belonging to 14 families were identified, namely Phlyctis argena, Punctelia jeckeri, Dyplolabia afzelii, Rhizocarpon lecanorinum, Phellinidium ferrugineofuscum, Cylindrobasidium laeve, Leptogium cyanescens, Trapelia coarctata, Trypethelium virens, Bacidia viridifarinosa, Ceriporia purpurea, Peniophora limitata, Lepraria finkii, and Dictyonema sericeum. Most species were found on tree trunks, with crustose thalli being the dominant type. The results of this study can serve as a source of scientific information on lichens in the Minanga Waterfall area and support the utilization of local resources as a source of biology education.